Evaluating physical environments for older people-Validation of the Swedish version of the Sheffield Care Environment Assessment Matrix for use in Finnish long-term care - Wahlroos Niina; Stolt Minna; Nordin Susanna; Suhonen Riitta (WILEY, 2022)
Aim: To validate a Finnish version of the Sheffield Care Environment Assessment Matrix (S-SCEAM) instrument for assessing the physical environment of long-term care settings and to describe the current status of the environmental quality of long-term care settings for older people in Finland.Background: The importance of providing a well-designed physical environment for older people is supported by the research literature. There is limited research of the physical environments of long-term care settings from the perspective of nursing science and nor is there much research into the instruments for assessing them.Design: A descriptive, correlational and observational study.Methods: Forward and back translation process was used followed by structured observations with S-SCEAM-Fin in 20 long-term care units in intensive residential care facilities for older people with 24-h nursing assistance and with extensive support for daily activities. Spearman's rho correlation, Cohen's kappa, percentage of agreement and Kuder-Richardson formula coefficients were calculated to assess psychometric properties of the translated S-SCEAM-Fin. S-SCEAM-Fin standardised scores were calculated to describe the current status of the environmental quality.Results: Inter-scale (domain) correlations showed low to moderate correlations between the domains. Consistency was acceptable in four of the domains. Cohen's kappa values indicated good (0.796 and 0.648) intra-rater and inter-rater (0.910 and 0.553) reliability. The overall mean of the standardised scores was 57.00, but there was variation between domains. Small units received the highest scores in the six domains.Conclusions: S-SCEAM-Fin was useful in assessing environmental quality. Assessment of the environmental quality disclosed deficiencies in ensuring settings adequate for older people.Implications for practice: The increasing numbers of older people with health conditions are residing in long-term care settings. It is essential to create supportive physical environments. The instrument can be useful when planning new facilities or proposing new recommendations for institutional living environments.